2022
DOI: 10.1111/bcp.15543
|View full text |Cite
|
Sign up to set email alerts
|

The impact of including a medication review in an integrated care pathway: A pilot study

Abstract: Aim:The objective of the present study was to measure the impact of the intervention of combining a medication review with an integrated care approach on potentially inappropriate medications (PIMs) and hospital readmissions in frail older adults.Methods: A cohort of hospitalized older adults enrolled in the French PAERPA integrated care pathway (the exposed cohort) was matched retrospectively with hospitalized older adults not enrolled in the pathway (unexposed cohort) between January 1st, 2015, and December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
1
1
0
Order By: Relevance
“…It can serve for the health care providers as a promising tool to improve the interdisciplinary and multiprofessional collaboration, especially as a digital solution that can realize its full potential [ 50 ]. Similar results have been reported in other countries [ 51 , 52 ]. In this study, participants suggested transferring medication-related information electronically and always in the format of the national medication plan.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It can serve for the health care providers as a promising tool to improve the interdisciplinary and multiprofessional collaboration, especially as a digital solution that can realize its full potential [ 50 ]. Similar results have been reported in other countries [ 51 , 52 ]. In this study, participants suggested transferring medication-related information electronically and always in the format of the national medication plan.…”
Section: Discussionsupporting
confidence: 92%
“…In the participating hospital, this strategy has been implemented during the project. For older patients in particular, shared medication records have the potential to reduce hospital readmissions [ 51 ].…”
Section: Discussionmentioning
confidence: 99%